2018
DOI: 10.5194/acp-18-14585-2018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relative humidity on the heterogeneous oxidation of secondary organic aerosol

Abstract: Abstract. Secondary organic aerosol (SOA) is a complex mixture of hundreds of semi-volatile to extremely low-volatility organic compounds that are chemically processed in the atmosphere, including via heterogeneous oxidation by gas-phase radicals. Relative humidity (RH) has a substantial impact on particle phase, which can affect how SOA evolves in the atmosphere. In this study, SOA from dark α-pinene ozonolysis is heterogeneously aged by OH radicals in a flow tube at low and high RH. At high RH (RH =89 %) the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 81 publications
1
35
0
1
Order By: Relevance
“…17,18 There is a wealth of research into the effects of this phenomenon on chemical and physical aerosol processes and includes, in part, aerosol growth after nucleation, [19][20][21] condensed phase reactions in secondary organic aerosol, 22 water uptake and ice nucleation 7 and preservation and transport of biomass burning tracer compounds 23 or pollutants. 13,24 Oxidants such as OH [25][26][27][28][29][30][31][32][33][34][35] and O 3 36-41 reacting with micrometer and submicrometer sized organic aerosol particles in a humidified environment have been previously observed and modeled to increase our understanding of how these small molecules may diffuse through and react within atmospheric particles. Further studies have made great strides in developing model frameworks to describe experimental data, including modeling of chemical reactions at the surface and within the bulk of aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 There is a wealth of research into the effects of this phenomenon on chemical and physical aerosol processes and includes, in part, aerosol growth after nucleation, [19][20][21] condensed phase reactions in secondary organic aerosol, 22 water uptake and ice nucleation 7 and preservation and transport of biomass burning tracer compounds 23 or pollutants. 13,24 Oxidants such as OH [25][26][27][28][29][30][31][32][33][34][35] and O 3 36-41 reacting with micrometer and submicrometer sized organic aerosol particles in a humidified environment have been previously observed and modeled to increase our understanding of how these small molecules may diffuse through and react within atmospheric particles. Further studies have made great strides in developing model frameworks to describe experimental data, including modeling of chemical reactions at the surface and within the bulk of aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have made great strides in developing model frameworks to describe experimental data, including modeling of chemical reactions at the surface and within the bulk of aerosol particles. 29,32,35,36,[42][43][44][45][46][47][48][49][50][51][52] In Shiraiwa et al, 36 the chemical half life of amino acids in thin films of bovine serum albumin (BSA) at a relative humidity, RH, of 90% and temperature, T, of 25 1C was determined to be about 5 min and increased to over an hour when RH o 50%. These authors used the kinetic multilayer model for aerosol surface and bulk chemistry (KM-SUB) to attribute this RH dependence on inhomogeneous mixing of reactants and products and calculated that at RH = 50%, the BSA diffusion coefficient was 10 À20 cm 2 s À1 with a viscosity close to that of a glass, 36 typically greater than 10 12 Pa s. [53][54][55] Ozone had a diffusion coefficient of 10 À9 cm 2 s À1 and was predicted only to be present and reacting in the first tens of nanometers of the BSA films.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical and physical transformations of SOA are often studied using atmospheric simulation chambers or oxidative flow reactors (e.g. Bloss et al, 2005;Cocker et al, 2001;Friedman and Farmer, 2018;Glowacki et al, 2007;Hamilton et al, 2011;Hodshire et al, 2018;Liu and Zeng, 2018;Rohrer et al, 2005;Witkowski et al, 2018). These techniques allow SOA formation and ageing to be investigated under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the solid condensed phase showed significantly lower γ O 3 values compared to the ozonolysis of the liquid phase. Recent experimental studies focused on how relative humidity (RH) influences the reactive uptake of gas oxidants via its impact on the phase state of the organic species (Berkemeier et al, 2016;Steimer et al, 2015;Shiraiwa et al, 2011;Slade and Knopf, 2014;Li et al, 2018;Davies and Wilson, 2015;Hu et al, 2016;Marshall et al, 2018). The heterogeneous oxidation of a typical component of biomass burning aerosol (BBA) particles, levoglucosan (LEV) by OH yielded γ values in the range from 0.008 to 1 with implications for the lifetime of LEV ranging from weeks at dry conditions (Slade and Knopf, 2013;Kessler et al, 2010;Slade and Knopf, 2014) to a couple of days when LEV is in a more https://doi.org/10.5194/acp-2020-82 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the depletion of citric acid and the formation of reaction products are confined near the aerosol-gas interface on the order of 8 nm at 20% RH, and the reaction depth increases to ~50 nm at 50% RH. Recently, Li et al (2018) observed that the heterogeneous aging of SOA by OH radicals at 89% RH and 25% RH resulted in ~60% and 20% loss of particle mass, respectively. The authors concluded that this difference in particle mass degradation is attributed to a larger OH uptake coefficient and/or larger fragmentation probability at higher RH.…”
Section: Introductionmentioning
confidence: 99%